Port hinterland intermodal container flow optimisation with green concerns : a literature review and research agenda - Lam, Jasmine Siu Lee (2013)
The closer link between ports and supply chain leads to a growing research area - port hinterland intermodal development. Focusing on the literature with mathematical models, the purpose of this paper is to categorise and analyse earlier research contributions on intermodal container flow optimisation, to identify the research trends and gaps, and to suggest future research directions. Results show that future research should focus on global intermodal container flow optimisation, addressing the approaches of ports integrating into such global intermodal chain taken green issues into account. There is substantial need for research addressing greening the intermodal network and sustainable development. Providing cost effective solutions alone in optimisation problem is rather traditional and one–sided. Those market players possessing commercially viable capabilities and also environmental responsibilities would gain a competitive advantage in future dynamic business environment. Bi–objective or multi–objective optimisation would be more suitable to actual situations.